Multi–spin echo spatial encoding provides three‐fold improvement of temperature precision during intermolecular zero quantum thermometry. Issue 5 (16th June 2015) - Davis, Ryan M.; Zhou, Zijian; Chung, Hyunkoo; Warren, Warren S.
Abstract : Purpose: Intermolecular multiple quantum coherences (iMQCs) are a source of MR contrast with applications including temperature imaging, anisotropy mapping, and brown fat imaging. Because all applications are limited by signal‐to‐noise ratio (SNR), we developed a pulse sequence that detects intermolecular zero quantum coherences with improved SNR. Methods: A previously developed pulse sequence that detects iMQCs, HOMOGENIZED with off resonance transfer (HOT), was modified with a multi‐spin echo spatial encoding scheme (MSE‐HOT). MSE‐HOT uses a series of refocusing pulses to generate a stack of images that are averaged in postprocessing for higher SNR. MSE‐HOT performance was quantified by measuring its temperature accuracy and precision during hyperthermia of ex vivo red bone marrow samples. Results: MSE‐HOT yielded a three‐fold improvement in temperature precision relative to previous pulse sequences. Sources of improved precision were 1) echo averaging and 2) suppression of J‐coupling in the methylene protons of fat. MSE‐HOT measured temperature change with an accuracy of 0.6°C. Conclusion: MSE‐HOT improved the temperature accuracy and precision of HOT to a level that is sufficient for hyperthermia of bone marrow. Magn Reson Med 75:1958–1966, 2016. © 2015 Wiley Periodicals, Inc.